Caecidotea camaxtli (Isopoda: Asellidae) a new species from the Tlaxcala valley, Mexico - García-Vázquez, Leonardo; Rodríguez-Almaraz, Gabino; Pedraza-Lara, Carlos (Zootaxa, 2019)
A new freshwater isopod, Caecidotea camaxtli sp. nov. (Isopoda, Asellidae) is described from Mexico. The new species can be distinguished from all other species of Caecidotea by the presence of cuticular scales on the caudal process, as well as a short and simple cannula in the apex of the endopodite of pleopod II. [Zoobank URL: urn:lsid:zoobank.org:act:082CF870-ABC3-4E25-B5F2-8CA59359C2B0]